Systemic Inflammatory Molecules Are Associated with Advanced Fibrosis in Patients from Brazil Infected with Hepatitis Delta Virus Genotype 3 (HDV-3) - Mauricio Souza Campos; Juan Miguel Villalobos-Salcedo; Deusilene Souza Vieira Dallacqua; Caio Lopes Borges Andrade; Roberto José Meyer Nascimento; Songeli Menezes Freire; Raymundo Paraná; Maria Isabel Schinoni (Microorganisms, 2023)
Background and Aims: Hepatitis Delta virus (HDV) genotype 3 is responsible for outbreaks of fulminant hepatitis in Northeastern South America. This study investigates if systemic inflammatory molecules are differentially expressed in patients with advanced fibrosis chronically infected with Hepatitis Delta virusgenotype 3(HDV-3). Methods: Sixty-one patients from the north of Brazil coinfected with hepatitis B virus (HBV)/HDV-3 were analyzed. HDV quantification and genotyping were performed by semi-nested real-time polymerase chain reaction (RT-PCR) and restriction fragment length polymorphism (RFLP) methodologies. Ninety-two systemic inflammatory molecules (SIMs) were measured by Proximity Extension Assay (PEA) technology. The Shapiro–Wilk, Student’s t-test, Mann–Whitney tests, and logistic regression analysis were used when appropriate. Results: The median age was 41 years, and all patients were HBeAg negative. Advanced fibrosis or cirrhosis was diagnosed by histological staging in 17 patients, while 44 presented with minimal or no fibrosis. Advanced necroinflammatory activity correlated positively with serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Established non-invasive fibrosis scores (APRI, FIB-4, and AST/ALT ratio) revealed low sensitivities and positive predictive values (PPVs) with an AUROC maximum of 0.586. Among the 92 SIMs analyzed, MCP.4, CCL19, EN.RAGE, SCF, and IL18 showed a positive correlation with fibrosis stage. A combined score including CCL19 and MCP.4 revealed a sensitivity of 81% and an odds ratio of 2.202 for advanced fibrosis. Conclusions: Standard non-invasive fibrosis scores showed poor performance in HDV-3 infection. We here suggest that the determination of CCL19 and MCP.4 may be used to identify patients with advanced fibrosis. Moreover, this study gives novel insights into the immunopathogenesis of HDV-3 infection.